2020
DOI: 10.1039/d0ta01033b
|View full text |Cite
|
Sign up to set email alerts
|

An environmentally adaptive quasi-solid-state zinc-ion battery based on magnesium vanadate hydrate with commercial-level mass loading and anti-freezing gel electrolyte

Abstract: A quasi-solid-state zinc-ion battery exhibits remarkable areal and volumetric energy/power densities and excellent cyclability from −30 to 60 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(50 citation statements)
references
References 72 publications
2
47
1
Order By: Relevance
“…According to the Nyquist plots in Figure 1E , the ionic conductivity values of gel electrolytes can be calculated. The calculation details can be found in our previous reports (Chen et al, 2020 ; Zhou et al, 2020 ). At a temperature of 20°C, the PAM/GO/EG gel electrolyte demonstrates a high ionic conductivity of 19.8 mS cm −1 , which drops to 17.9 and 14.9 mS cm −1 when the temperature declines to 0 and −20°C, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Nyquist plots in Figure 1E , the ionic conductivity values of gel electrolytes can be calculated. The calculation details can be found in our previous reports (Chen et al, 2020 ; Zhou et al, 2020 ). At a temperature of 20°C, the PAM/GO/EG gel electrolyte demonstrates a high ionic conductivity of 19.8 mS cm −1 , which drops to 17.9 and 14.9 mS cm −1 when the temperature declines to 0 and −20°C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, energy-storage devices are required to work in low-temperature environments, since it is cold in winter in many regions around the world. It has been reported that adding cryoprotectants such as glycerol and ethylene glycol (EG) into gel electrolytes can realize good anti-freezing capabilities (Mo et al, 2019 ; Zhou et al, 2020 ). In our previous report, we developed a borax-cross-linked PVA/glycerol gel electrolyte, in which glycerol can interact with PVA chains strongly, thus effectively preventing the formation of ice crystals within the whole gel network (Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, glycerol/water also shows good freeze‐resistant property for zinc metal energy storage devices. A PVA/glycerol anti‐freezing gel electrolyte with an ionic conductivity of 10.7 mS cm −1 at −30 °C was reported by Wong and coworkers [31c] . The Zn−δ−MgVO battery assembled with this electrolyte can work from −30 °C to 60 °C.…”
Section: Design Of Anti‐freezing Electrolytesmentioning
confidence: 90%
“…Wong et al. reported a Mg 0.19 V 2 O 5 ⋅ 0.99H 2 O material for anti‐freezing zinc‐ion batteries (Figure 6c) [31c] . Mg 2+ and H 2 O molecules acted as pillars between the layers to stabilize the structure during charge and discharge.…”
Section: Low‐temperature‐resistant Cathode Materialsmentioning
confidence: 99%
“…Further investigation manifested that fabricated battery exhibited robustness and flexibility which can light up LED lights. Wong [ 133 ] and co‐workers [ 134 ] also developed poly(vinyl alcohol) (PVA)/glycerol gel electrolyte which exhibits anti‐freezing ability (Figure 15b). The borax crosslinking in the framework strongly interact with PVA chains, hence effectively prohibiting the formation of ice crystals within the whole gel network.…”
Section: Hybrid Polymer Electrolytesmentioning
confidence: 99%